Penggunaan Bahasa Ogan di Desa Makarti Tama SP 5 Blok C Peninjauan OKU: Kajian Pemertahanan Bahasa - Awalludin, Awalludin; Nilawijaya, Rita; Inawati, Inawati; Anggraini, Tri Riya (Bastrando: Jurnal Bahasa dan Sastra Indonesia, 2024)
The aim of this study is to determine how the use of language in the village Ogan makarti Tama SP 5 in the current situation or the current state as well as to describe Ogan How is retention language in the village of Tama makarti SP 5 Block C District A review. The method used in this research is descriptive method, namely the attempt to describe and interpret the complete retention of the language with dialect or patois see speech and language attitudes, speech community in the village of Tama makarti Ogan which includes the use of language in formal and informal situations. Based on the results of data analysis has been done to the component author sociolinguistics in language use Ogan in the village of Makarti Tama can be concluded that the language used in speaking Ogan village of Tama is makarti Ogan and Indonesian languages​​. Ogan language used in informal and formal situations, while Indonesian is used in formal situations.